Gain of chromosome 1q21 is an independent adverse prognostic factor in light chain amyloidosis patients treated with melphalan/dexamethasone. (March 2014) - Bochtler, Tilmann; Hegenbart, Ute; Kunz, Christina; Benner, Axel; Seckinger, Anja; Dietrich, Sascha; Granzow, Martin; Neben, Kai; Goldschmidt, Hartmut; Ho, Anthony D.; Hose, Dirk; Jauch, Anna; et al.
Abstract Chromosomal aberrations of plasma cells are well established pathogenetic and prognostic factors in multiple myeloma, but their prognostic implication in systemic light chain (AL) amyloidosis is unclear. Therefore, the aim of this study was to identify prognostic cytogenetic risk factors by interphase FISH in a series of 103 consecutive AL amyloidosis patients treated uniformly with melphalan/dexamethasone as first-line therapy. Detection of gain of 1q21 was predictive for a poor overall survival (OS) (median 12.5 versus 38.2 months, p = 0.002). Hematologic event free survival (hem EFS) for gain of 1q21 was 5.0 versus 8.5 months in median (p = 0.08) and haematologic remission rates (≥VGPR) after three cycles were 5% versus 25% (p = 0.06). Most important, in multivariate concordance analyses the adverse prognosis carried by gain of 1q21 was retained as an independent prognostic factor (OS: p = 0.003, average hazard ratio (AHR) = 3.64, hemEFS: p = 0.008, AHR = 2.35), along with the well established Mayo cardiac staging. Patients with t(11;14) had a longer median OS with 38.2 months versus 17.5 months, though no statistical significance was reached. Deletion 13q14 and hyperdiploidy turned out to be prognostically neutral. In conclusion, we have identified gain of 1q21 as an independent adverse prognostic factor in AL amyloidosis patients treated with standard chemotherapy.